Effect of Probiotic on Beneficial and Pathogenic Microorganisms in the Gastrointestinal Tract of Commercial Broiler with BCRDV Vaccine (Progressive Agriculture, 2014)
The present study was conducted to determine the effect of probiotic on beneficial and pathogenic microorganisms in the gastrointestinal tract of Commercial Broiler. A total of 80 day-old broiler chicks were divided into two main groups I and II with 40 chicks in each. Group I was supplemented with Probiotic (Saccharomyces cerevisiae 2 gm/kg feed) containing feed and chicks of group II was supplemented with conventional feed. Group I and II was again subdivided into two subgroups as group A, B and C, D respectively on 6 days of age. Birds of subgroups A and C were vaccinated with ND vaccine (BCRDV) and birds of subgroups C and D were kept as unvaccinated. The result evidenced the following information: (a) The total viable count (TVC) and total coliform count (TCC) were significantly (P